The Behavior of Elite Voters in The Election of Regional Heads - Ninda Cyntia; Tomi Oktavianor (Asean Study Center Lambung Mangkurat University, 2022)
Researchers used descriptive qualitative methods and three data collection techniques, namely observation, interviews, documents related to the research, and key informants, including voters, religious leaders, and Damang (traditional leaders). The data processing procedure is to collect data first, then reduce the data, present the data, and draw conclusions. The results of the study show that elite voters choose because of the factors of position, education, work, and religion. It is the sociological approach that voters tend to use. This is due to the fact that voters base their decision on the candidate's figure more than anything else. factors of the community determine their political choices, especially on the religious side. They are more likely to choose based on the similarity of their religion. Voters tend to see the figure of the candidate as being given a gift, even though it may be in the form of money or goods, which is not enough to influence someone's decision to make a choice. Voters' orientation to developing issues, especially socio-political ones, and one's orientation to candidates, as well as choosing self-direction with which alternative is the maximum for him, is a consideration in choosing a candidate.